Australian Unity in Judith Wright’s Selected Ecopoems - Farajallah, Noor Zeid; Lewis, Anan J. (Al-Adab Journal, 2021)
Judith Wright's (1915-2000) concern about man's disintegration with the natural world and the horror of the destruction of the earth reflects a high sense of ecological awareness caused by the threat of pollution that pervades the environment. Wright's ecopoetry draws attention to the danger of displacing oneself from the natural world that would also cause an inner alienation in man. The purpose of this paper is to explore Wright’s ecopoetical representation of the Australian ecology and its integral connection with Australia’s national unity. As the study examines Wright’s various volumes of poems, it argues that the lack of ecological awareness weakens the national and social fabric of Australia and deteriorates its environment. It also asserts that the poet’s ecopoetic quest for preserving the Australian ecology generates a new articulation of the Australian cultural identity and nationhood.